2019
DOI: 10.35940/ijrte.c6196.098319
|View full text |Cite
|
Sign up to set email alerts
|

Surface Corrosion Grade Classification using Convolution Neural Network

Abstract:  Abstract: Corrosion is a prevalent issue in the oil and gas industry. Usually, pipelines made of Iron are used for oil and gas transportation. The pipelines are large and distributed over big fields above the ground, underground and even underwater. Corrosion gets developed because of environmental variables such as temperature, humidity and acidic nature of the liquids. There are different techniques for detecting and monitoring corrosion development, both destructive and non-destructive. Visual inspection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…While many authors have dealt with deep learning algorithms to deal with corrosion detection issues [15], [21], [31]- [35], few scientists have focused on classifying corrosion types in different environments [13], [16], [22], [36], [37]. More importantly, no work has been done to classify corrosion types for ASTs, and using EfficientNet architectures.…”
Section: Discussion and Comparison With The State-of-the-artmentioning
confidence: 99%
“…While many authors have dealt with deep learning algorithms to deal with corrosion detection issues [15], [21], [31]- [35], few scientists have focused on classifying corrosion types in different environments [13], [16], [22], [36], [37]. More importantly, no work has been done to classify corrosion types for ASTs, and using EfficientNet architectures.…”
Section: Discussion and Comparison With The State-of-the-artmentioning
confidence: 99%
“…The prevention of corrosion using paint coatings is a common practice for physical infrastructure including bridges, marine vessels, pipelines and electricity towers. Thus early detection of failing paintwork is an important inspection requirement with a wide range of applications for which research on automating image analysis has been reported in the literature [3]- [7]. For corrosion assessment, colour and texture features have been used.…”
Section: Related Workmentioning
confidence: 99%
“…A CNN comprises of various convolutional layers, pooling layers and completely associated layers followed by one order layer [2]. At the point when the size of the image is given as contribution to the CNN include maps are delivered by convolving the image with the channels [3]. Each guide is sub-tested regularly with mean or max pooling layers.…”
Section: Introductionmentioning
confidence: 99%